2008
DOI: 10.4319/lom.2008.6.246
|View full text |Cite
|
Sign up to set email alerts
|

Naturally present fatty acids as internal calibrants for Fourier transform mass spectra of dissolved organic matter

Abstract: The analysis of dissolved organic matter (DOM) by Fourier transform ion cyclotron resonance mass spectrometry (FTICR-MS) has gained wide interest recently, driven primarily by its ultrahigh resolving power and mass accuracy. Accurate calibration of mass spectra is a key step to successfully decipher the DOM components. We propose a simple and accurate method to internally calibrate the peaks in the complex spectra without the need to add a calibrant. Mass spectra of DOM samples from the Dismal Swamp, Virginia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 39 publications
1
75
0
Order By: Relevance
“…All of the acquired FTICR mass spectra were similar to DOM samples analyzed previously [14,23,[33][34][35][36]38], with most peaks existing at 300-600 m/z. The majority of peaks appear at odd m/z values, and, based upon the nitrogen rule, indicate a predominance of zero or an even number of nitrogens in the molecules.…”
Section: Characterization From Fticr-ms Measurementssupporting
confidence: 54%
See 1 more Smart Citation
“…All of the acquired FTICR mass spectra were similar to DOM samples analyzed previously [14,23,[33][34][35][36]38], with most peaks existing at 300-600 m/z. The majority of peaks appear at odd m/z values, and, based upon the nitrogen rule, indicate a predominance of zero or an even number of nitrogens in the molecules.…”
Section: Characterization From Fticr-ms Measurementssupporting
confidence: 54%
“…Prior to data analysis, all samples were externally calibrated with a polyethylene glycol standard and internally calibrated with fatty acids, dicarboxylic acids, and other naturally present compounds that are part of various CH 2 homologous series [33]. All m/z lists, created using a signal to noise threshold of 3, were exported for further analysis.…”
Section: Fticr-ms Analysismentioning
confidence: 99%
“…The instrument was externally calibrated daily using a polyethylene glycol standard. Each spectrum was internally calibrated using the naturally occurring molecules including fatty acids and other homologous series of compounds containing only carbon, hydrogen and oxygen [38]. Peaks consistent with salts (mass defect 0.4-0.98 for m/z < 400, and mass defect 0.6-0.97 for m/z > 400), blank peaks (those found in the respective filter blank), and 13 C isotopologue peaks were subtracted from the mass list and not considered for formula assignments.…”
Section: Fticr-ms Analysismentioning
confidence: 99%
“…Admittedly, exact masses and molecular formulae are insufficient proof of structure, because many possible isomeric compounds share these characteristics. Sleighter et al (2008) have shown recently that some peaks in the FTICR mass spectrum of dissolved organic matter have the exact masses of fatty acids, and they have assumed that these peaks are attributable to fatty acids. Certainly, seawater is known to contain fatty acids (McCallister et al, 2006), and fatty acids are much more readily ionized using FTICR-MS in negative ion mode than non-acidic compounds having the same molecular formulae, so it is reasonable to assume that these peaks actually are fatty acids.…”
Section: Fourier Transform Ion Cyclotron Resonance (Fticr) Mass Spectmentioning
confidence: 99%